2021
DOI: 10.13057/biodiv/d220624
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and cytological studies of the Genus Amomum Roxb. former Elettariopsis Baker (Zingiberaceae) in Thailand

Abstract: Abstract. Saensouk P, Saensouk S. 2021. Diversity and cytological studies on the genus Amomum Roxb. former Elettariopsis Baker (Zingiberaceae) in Thailand. Biodiversitas 22: 3209-3218. A comprehensive diversity and cytological studies of the genus Amomum Roxb. in Thailand have not been reported. This work aims to study the diversity and cytological including chromosome numbers and karyotypes of the genus Amomum Roxb. former Elettariopsis Bakerin Thailand. Ten species of Amomum were recognized from Thailand. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…This research demonstrates that a somatic chromosome number of 2n = 22 is the most common in Kaempferia, consistent with previous studies [5,[12][13][14][15][16][17][18][19][20][21][22][23][24]. The five species studied, Kaempferia minuta, K. phuphanensis, K. sisaketensis, K. takensis, and K. udonensis, also had somatic chromosome numbers of 2n = 22.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This research demonstrates that a somatic chromosome number of 2n = 22 is the most common in Kaempferia, consistent with previous studies [5,[12][13][14][15][16][17][18][19][20][21][22][23][24]. The five species studied, Kaempferia minuta, K. phuphanensis, K. sisaketensis, K. takensis, and K. udonensis, also had somatic chromosome numbers of 2n = 22.…”
Section: Discussionsupporting
confidence: 90%
“…Chromosome morphology can provide valuable data to better understand phylogenetic relationships among various taxa [10,11]. Previous studies have shown that the basic chromosome number in Kaempferia is x = 11, with polyploidy and aneuploidy occurring among the different species, including K. angustifolia (2n = 33), K. elegans (2n = 22 and 33), K. filifolia (2n = 22), K. galanga (2n = 55), K. koratensis (2n = 44), K. larsenii (2n = 22), K. marginata (2n = 44), K. parviflora (2n = 22), K. pulchra (2n = 22), K. roscoeana (2n = 22), K. rotunda (2n = 22 and 33), K. saraburiensis (2n = 22), and K. siamensis (2n = 22), and their karyotype formulae has not been reported before [5,[12][13][14][15][16][17][18][19][20][21][22][23][24]. To date, the chromosome number and karyology of K. minuta, K. phuphanensis, K. sisaketensis, K. takensis, and K. udonensis are unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diploid chromosome numbers of each specimen in this study were counted from 20 cells. For the arrangement of the karyotypes, the following parameters, such as average length of the short arm (Ls), average length of the long arm (Ll), length of each chromosome (LT), average measurement of relative length (RL), chromosome index (CI), standard deviation (SD) of RL and CI from metaphase chromosomes, were calculated by the methods of Saensouk et al (2019), Senavongse et al (2018;2020), Saensouk and Saensouk (2021a) and Saensouk and Saensouk (2021b).…”
Section: Methodsmentioning
confidence: 99%